The Replacement of Missing Values of Continous Air Pollution Monitoring Data using Mean Top Bottom Imputation technique - Norazian, Mohamed Noor; Ahmad Shukri, Yahaya; Nor Azam, Ramli; Mohd Mustafa, Al Bakri Abdullah (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my